L’élévation du niveau de la mer menacerait-elle le littoral de la Martinique ? L’exemple de la commune du Prêcheur - Pascal Saffache; Yoann Pelis (Études Caribéennes)
Although it has contributed very little to global air pollution, Martinique - like the Caribbean micro-island territories - will be hard hit by climate change in general and sea level rise in particular.Optimistic forecasts predict that Martinique will lose 5% of its area by the end of this century, while pessimistic forecasts indicate that it will lose 9 to 10%. Whatever the situation, it will be necessary to set up a real policy of protection of the populations living on the coastal margins, even of the displacement of the latter. The example of the commune of Prêcheur (North of Martinique), a precursor in this field, will be deciphered, because it is likely to become a real model.